Effect of Pre-operative Parenteral Testosterone on Penile Dimensions and Vascularity in Proximal Hypospadias: A Prospective Observational Study - Md Mokarram Ali (Wolters Kluwer Medknow Publications, 2024)
Introduction: Severe or proximal hypospadias is associated with inadequate local tissue and small phallus size. Pre-operative androgens have been used to increase phallus size, but there are very few studies on its role in proximal hypospadias. This study aimed to assess the effects of pre-operative intramuscular (IM) testosterone on proximal penile hypospadias in terms of penile morphology and tissue characteristics of penile skin. Materials and Methods: This prospective observational study was conducted on 27 patients of proximal hypospadias over a period from June 2017 to July 2018. The patients were sequentially enrolled into two groups: Group A and Group B. Group A patients received IM testosterone before surgery, whereas Group B patients were operated without pre-operative testosterone. Outcomes were analysed in terms of change in penile dimensions and effect on vascularity of penile skin. Results: Pre-operative IM testosterone in Group A caused a significant increase in stretched penile length from a mean of 3.058 cm (±0.691) to 3.9 cm (±0.875) (P = 0.002), penile circumference from a mean of 4.142 cm (±0.772) to 4.667 cm (±1.174) (P = 0.029) and glans width from a mean of 1.225 cm (±0.245) to 1.750 cm (±0.571) (P = 0.002). There was higher microvessel density in the preputial skin of Group A (mean: 12.212 [±4.745] blood vessels/high-power field [HPF]) compared to Group B (8.867 [±3.258] blood vessels/HPF) (P = 0.043). Conclusion: Pre-operative testosterone in proximal hypospadias causes significant changes in penile dimensions and tissue characteristics. Improvement in penile dimensions leads to ease in operability and better tissue handling. However, more studies with large sample size are required to establish the beneficial effects of pre-operative hormone stimulation on urethroplasty.